Investigating the Factors Related to the Success of Forced Eruption Treatment of Impacted Maxillary Canine Teeth - Reza Namadkolahi; Mahdiye Maratebi; Sara Faraj Vajari; Parastoo Ghaderi; Niloofar Deravi; Sohrab Pourkhamaneh; Pouyan Sigari (Indonesian Journal of Dentistry, 2026)
Background: The maxillary canine is often more difficult to manage orthodontically compared to other teeth.Objective: This study aims to evaluate additional factors affecting the success of Forced Eruption treatment for impacted maxillary canines, emphasizing the importance of timely and appropriate therapeutic strategies.Method: This descriptive-analytical study evaluated the records of 52 patients diagnosed with maxillary canine impaction. Data sources included Cone Beam Computed Tomography (CBCT) images and initial and final panoramic radiographs available in the patients' files. The collected data were analyzed using SPSS software.Outcome: The study revealed a significant relationship between the depth of impaction and the success of Forced Eruption treatment for maxillary impacted canines (p < 0.05). However, no significant associations were found between the success of the treatment and variables such as age, gender, position of impaction, or the available space in the maxillary arch. These findings suggest that depth of impaction is a critical factor influencing treatment outcomes, while other demographic and positional factors may not significantly affect success rates.Conclusion: Patients with a lower depth of maxillary canine impaction experience better outcomes with Forced Eruption treatment